Informal finance in China : American and Chinese perspectives - Li, Jianjun; Hsu, Sara. (New York ; Oxford : Oxford University Press, 2009)
This is a compilation of chapters written by leading scholars on informal, or non-bank, finance in China. Presently there is a scarcity of information on informal finance in China, and yet by heavily interacting with bank financing and production, informal finance is estimated to have a significant impact upon GDP and the money supply.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Finance -- China; Financial institutions -- China; Informal sector (Economics) -- China